Factors explaining tobacco use among young people in the Ngaba health zone: The case of the Mukulua health area and proposed health education components. - Jacques; Gérard; Bob Senker Ndimba; Emmanuel; Mbadu; Jean-Paul; Jules (Student's Journal of Health Research Africa, 2026)
Introduction Smoking among young people is a major public health problem. In Mukulua, social environment, peer influence, pleasure, taste, and stress contribute to tobacco use. This study aimed to identify sociodemographic, social, and behavioral factors associated with smoking and to propose appropriate health education, including prevention and smoking cessation. Methods A descriptive cross-sectional analytical study was conducted from May 23 to June 25, 2026, in the Mukulua Health Area among 384 young people aged 15–30 years. Convenience sampling was used. Data were collected through a questionnaire following a pre-survey and informed consent, while maintaining confidentiality. Results The study found that 83.6% of young people had smoked previously, with males predominating. The social environment was the main source of information (96%). The main reasons for smoking were peer influence (33.3%), pleasure and taste (29.3%), and stress (22.1%). Age, occupation, and marital status were significantly associated with smoking. Discussion Smoking among young people in Mukulua was mainly associated with peer influence, pleasure, taste, and stress. Age, occupation, and marital status also showed significant associations. Despite good knowledge of the health risks, smoking prevalence remained high and cessation was difficult. Conclusion Smoking among young people in Mukulua is multifactorial, mainly associated with peer influence, pleasure, stress, and certain sociodemographic characteristics. Despite awareness of the risks, tobacco use remains high and quitting is difficult. Integrated, participatory, and youth-friendly health education is therefore needed.